Evaluate \(\left(8^{-3}\right)^{\frac{1}{3}}\)
Simplify the exponent
\(\left(8^{-3}\right)^{\frac{1}{3}} = 8^{-3 \cdot \frac{1}{3}} = 8^{-1}\)
Evaluate \(8^{-1}\)
\(8^{-1} = \frac{1}{8}\)
\(\boxed{\left(8^{-3}\right)^{\frac{1}{3}} = \frac{1}{8}}\)
Evaluate \((\sqrt[3]{64})^{2}\)
Simplify \(\sqrt[3]{64}\)
\(\sqrt[3]{64} = 4\)
Square the result
\(4^{2} = 16\)
\(\boxed{(\sqrt[3]{64})^{2} = 16}\)
Evaluate \(\sqrt[4]{\frac{1}{16}}\)
Simplify the fourth root
\(\sqrt[4]{\frac{1}{16}} = \left(\frac{1}{16}\right)^{\frac{1}{4}}\)
Express \(\frac{1}{16}\) as a power of 2
\(\frac{1}{16} = 2^{-4}\), so \(\left(2^{-4}\right)^{\frac{1}{4}} = 2^{-1} = \frac{1}{2}\)
\(\boxed{\sqrt[4]{\frac{1}{16}} = \frac{1}{2}}\)
Evaluate \(\left(\sqrt[3]{\frac{1}{8}}\right)^{2}\)
Simplify \(\sqrt[3]{\frac{1}{8}}\)
\(\sqrt[3]{\frac{1}{8}} = \frac{1}{2}\)
Square the result
\(\left(\frac{1}{2}\right)^{2} = \frac{1}{4}\)
\(\boxed{\left(\sqrt[3]{\frac{1}{8}}\right)^{2} = \frac{1}{4}}\)
\(\boxed{\left(8^{-3}\right)^{\frac{1}{3}} = \frac{1}{8}}\)
\(\boxed{(\sqrt[3]{64})^{2} = 16}\)
\(\boxed{\sqrt[4]{\frac{1}{16}} = \frac{1}{2}}\)
\(\boxed{\left(\sqrt[3]{\frac{1}{8}}\right)^{2} = \frac{1}{4}}\)
The expressions equivalent to \(\frac{1}{4}\) are:
\(\boxed{\left(\sqrt[3]{\frac{1}{8}}\right)^{2}}\).